2013
DOI: 10.1089/vbz.2012.1102
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferisensu lato Infecting Ticks of theIxodes ricinusComplex in Uruguay: First Report for the Southern Hemisphere

Abstract: The Borrelia burgdorferi sensu lato (s.l.) group comprises genetically related spirochetes, mostly associated with tick species belonging to the Ixodes ricinus complex in the Northern Hemisphere. The present study evaluated borrelial infection in the tick Ixodes pararicinus, which is the only representative species of the I. ricinus complex in Uruguay. A total of 137 I. pararicinus ticks were collected from deer, cattle, or vegetation in 2 Uruguayan Departments. A part of these ticks was tested directly by PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 27 publications
4
35
0
4
Order By: Relevance
“…Our results are in the line with other Borrelia detections published for the South American fauna of ticks (Parola et al 2011, Barbieri et al 2013, Sebastian et al 2016, Dall'Agnol et al 2017, and demonstrates that the diversity of spirochetes of this genus is currently underestimated for the region.…”
Section: Borreliasupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in the line with other Borrelia detections published for the South American fauna of ticks (Parola et al 2011, Barbieri et al 2013, Sebastian et al 2016, Dall'Agnol et al 2017, and demonstrates that the diversity of spirochetes of this genus is currently underestimated for the region.…”
Section: Borreliasupporting
confidence: 93%
“…While in 1995, detection of LDG borreliae DNA in seabird ticks (i. e. Ixodes uriae White 1852) confirmed the presence of this bacteria in insular territories of the Southern Hemisphere (Olsen et al 1995, Gylfe et al 2001, it was only in recent years that molecular evidence (Barbieri et al 2013, Sebastian et al 2016, Dall'Agnol et al 2017, and the isolation of Borrelia chilensis (Ivanova et al 2014), demonstrated that LDG spirochetes do occur in South America. Conversely, the knowledge of RFG borreliae in this region of the American continent dates from the first half of 20 th century, when experimental research on soft tick-borne borreliae enabled the documentation of several RFG species , Davis 1952.…”
Section: Identities and Phylogenetic Position Of Soft Tick Rickettsiamentioning
confidence: 97%
“…The I. ricinus species complex is represented in 43 South America by Ixodes pararicinus, Ixodes affinis (this species is 44 also present in the Nearctic) and Ixodes aragaoi (Venzal et al, 2005;45 Onofrio et al, 2014), and possibly also by Ixodes fuscipes, as records of these four species biting humans along their distribution 48 in this continent (Guglielmone et al, 2014). 49 The only consistent reports of B. burgdorferi s.l in South America 50 were made in Chile and Uruguay (Barbieri et al, 2013;Ivanova 51 et al, 2013). Borrelia chilensis was described in Chile throughout 52 the characterization of cultured spirochetes and borrelial DNA 53 obtained from Ixodes stilesi ticks collected in Valdivia, Chile 54 (Ivanova et al, 2013).…”
mentioning
confidence: 95%
“…Borrelia chilensis was described in Chile throughout 52 the characterization of cultured spirochetes and borrelial DNA 53 obtained from Ixodes stilesi ticks collected in Valdivia, Chile 54 (Ivanova et al, 2013). In Uruguay, specimens of I. aragaoi (named as 55 I. pararicinus, see Onofrio et al (2014)) were found to be infected 56 with two new genospecies of B. burgdorferi s.l, one phylogenetically 57 related to B. bisettii and the other associated to B. americana 58 (Barbieri et al, 2013). Cases of tick-borne borreliosis were not 59 diagnosed so far in both the countries.…”
mentioning
confidence: 99%
“…Partial molecular characterization of this agent indicates that it is most closely related to SFG rickettsial agents associated with I. affinis (LOPES et al, 2016), I. ricinus (MAIOLI et al, 2012), I. minor (OGRZEWALSKA et al, 2015), and I. scapularis (PAROLA et al, 2013). These four Ixodes species, as well as I. pararicinus, belong to the I. ricinus species complex, based primarily on morphological and genetic relatedness (KEIRANS et al, 1985;BARBIERI et al, 2013). Interestingly, recent studies have indicated that tick members of the I. ricinus species complex are usually infected by species-specific closely related rickettsial organisms, usually considered endosymbionts (KURTTI et al, 2015).…”
mentioning
confidence: 99%